Perceptions of English Teachers About Lesson Plans For The KTSP and The 2013 Curricula - Sofyan A. Gani; Teuku Zulfikar; Tri Sulisdawati (Universitas Syiah Kuala, 2017)
This study was aimed at investigating what the English teachers at SMAN 1 Banda Aceh felt about the KTSP (School-Based Curriculum) and the 2013 Curriculum, to find out the challenges faced by these English teachers at SMAN 1 Banda Aceh in creating lesson plans based on the KTSP and the 2013 Curriculum, and to find out what might help them to deal with these challenges. The participants in this research were two English teachers at SMAN 1 Banda Aceh who have been teaching both the KTSP and the 2013 Curriculum. Based on the interview results, the researchers found that the teachers felt that they were familiar with using English lesson plans for the KTSP but they needed more time and training in order to prepare English lesson plans for the 2013 Curriculum because it was still new to them. The researcher also found that the teachers did not face challenges in creating English lesson plans for the KTSP but they faced challenges in creating English lesson plan for the 2013 Curriculum mainly in terms of developing assessment rubrics and formulating indicators for the 2013 curriculum lesson plans. Furthermore, assistance for teachers to deal with these challenges in creating such English lesson plan could come from (i) consultation with fellow teachers, (ii) attending training and (iii) discussions with fellow English teachers at MGMP (Subject Teachers Meetings). Analysis of their English lesson plans showed that their designs had incomplete rubric assessments and they did not have time limits for their teaching-learning activities.